Exploring the Factor-Performance Relationship of Integrated Project Delivery Projects: A Qualitative Comparative Analysis. Issue 3 (June 2019) - Yu, Jung Ho; Yoo, Seung Eun; Kim, Jung In; Kim, Tae Wan
This study aims to explore the relationship between the critical success factors (CSFs) and the performance of integrated project delivery (IPD) projects based on empirical data from IPD projects. Data from 16 projects, in relation to 25 success factors and four performance areas (schedule performance, cost performance, defects, and change orders), were gathered and analyzed according to the qualitative comparative analysis method. As a result, this study identifies 17 factors as conditions that frequently occurred in successful IPD projects. This study also derives combinations of factors that led to IPD project success regarding each of the four performance areas.